Evolution of iron crust and clayey Ferralsol in deeply weathered sandstones of Marília Formation (Western Minas Gerais State, Brazil) - Rosolen, Vania [UNESP]; Bueno, Guilherme Taitson; Melfi, Adolpho José; Montes, Célia Regina; de Sousa Coelho, Carla Vanessa [UNESP]; Ishida, Débora Ayumi; Govone, José Silvio [UNESP] (Elsevier, 2017)
Extensive flat plateaus are typical landforms in the cratonic compartment of tropical regions. Paleoclimate, pediplanation, laterization, and dissection have created complex and distinct geological, geomorphological, and pedological features in these landscapes. In the Brazilian territory, the flat plateau sculpted in sandstone of Marília Formation (Neocretaceous) belonging to the Sul-Americana surface presents a very clayey and pisolitic Ferralsol (Red and Yellow Latossolo in the Brazilian soil classification). The clayey texture of soil and the pisolites have been considered as weathering products of a Cenozoic detritical formation which is believed to overlay the Marília Formation sandstones. Using data of petrography (optical microscopy and SEM), mineralogy (RXD), and macroscopic structures (description in the field of the arrangement of horizons and layers), a complete profile of Ferralsol with ferricrete and pisolites was studied. The complex succession of facies is in conformity with a sedimentary structure of Serra da Galga member (uppermost member of Marília Formation). The hardening hematite concentration appears as layered accretions in the subparallel clayey lenses of sandstone saprolite, preserving its structure. Iron contents varied according to different soil fabrics. Higher concentrations of iron are found in the massive ferricrete or in pisolites in the mottled horizon. Kaolinite is a dominant clay mineral and shows two micro-organizations: (1) massive fabric intrinsic to the sedimentary rock, and (2) reworked in pisolites and illuviated features. The pisolites are relicts of ferricrete in the soft bioturbated topsoil. The continuous sequence of ferricrete from saprolite to the Ferralsol indicates that the regolith is autochthonous, developed directly from sandstones of Marília Formation, through a long and intense process of laterization.
Keywords: Clayey Ferralsol; Ferricrete; Marília formation; Pisolites; Sandstone; South American surface